Efek Sekunder Pada Aliran Turbulen Terhadap Aliran Super Kritis Pada Saluran Terbuka Untuk Bangunan Penguras Sedimen Untuk Irigasi: Secondary Effects of Turbulent Flow on Supercritical Flow in Open Canal For Sediment Trap Structure for Irrigation - Isnaeni, Muhammad (Jurnal Teknik Sumber Daya Air, 2024)
Secondary influence on supercritical flow with a Froude number > 1, which flows at the bottom of the canal surface of the concrete lining, has a secondary effect, which causes contour line protrusions and velocity with a wavy pattern of the average velocity distribution across the wet perimeter. Supercritical flow can transition to sub-critical flow through a hydraulic jump phenomenon that is detrimental to flow rate. This research is recommended as an innovation for optimum discharge efficiency and flow depth parameters in an open canal in an irrigation system. This research method involves physical testing with a 1:40 scale flume on a prototype in the laboratory so that detailed profiles of instantaneous and vertical flow velocity are observed using a 16 Mhz Acoustic Doppler Velocimeter (ADV) to obtain flow characteristics. Then, the modified wake-log law on the bottom and surface of the flow is analysed in the flume within 5 hours of flow to determine the increase in the more stable sediment fraction per hour. The research results show that the ratio of width (b) and depth of flow (h) can significantly increase the strength of the secondary flow with an ideal b/h ratio that can provide discharge flow efficiency based on Froude number = 2.2 and Reynolds 2500 - 2600 can be efficient up to 46% is required Q: 1.26 l/s, flow speed 10.79 cm/s so that the flow is in a laminar to turbulent transition position and does not trigger sedimentation in the wet perimeter of the canal.